Burnout e Capital Psicológico: Uma Perspectiva Teórico-metodológica sobre Transição de Carreira de Estudantes - Matos, Fabíola Rodrigues (2021)
Students seeking to enter higher education face challenges that include social pressures, changes in personal life to achieve approval, decisions on course selection, preparation methods and a quest for optimizing content learning. This doctoral thesis sought, through four studies, to investigate the current situation of mental health and the personal resources of students who aim to enter higher education, the research points of this research being student burnout and psychological capital. In the first article, evidence of accuracy and precision wasraised for the Oldenburg Burnout Inventory - Student Version (OLBI-S) in the Brazilian context. The results indicated that an adapted version of OLBIS presents validity and reliability indicators for a two-dimensional structure (exhaustion and disengagement). In the second article, the Psychological Capital Scale in the Context of Studies (PsyCap-E) was elaborated and evidence of precision and precision of the instrument was presented. The results indicated good psychometric quality for an internal structure of four dimensions (resilience, hope, self-efficacy and optimism). In the third article, we sought to explore how career adaptability resources, psychological capital and mental health indicators (depression, anxiety and stress) predict student burnout. The results indicated that the perception of control and resilience help students not to experience exhaustion. They also showed that concern, anxiety, optimism and resilience prevent disengagement in the educational environment. Finally, the fourth article investigated student burnout, mental health aspects and their relationship with study habits and studies among students in Espírito Santo. The results indicated above-average levels for negative affects, depression and anxiety, as well as the association between exhaustion and the longest study time in the sample. Aspects related to interventions in the area and the need for additional research that adopt the longitudinal design to the development and monitoring of psychological resources for health promotion are discussed.